How Does Zakat Institutions Contribute to the Business Success of Mustahiq? - Muttaqien, Muhammad Khaerul; Mufraini, Muhammad Arief; Suherlan, Ade (Maliki Islamic Economics Journal, 2022)
The purpose of this study was to examine the effect of Zakat Institutions through funding and training provided by amil zakat institutions and mustahiq's knowledge on the success of mustahiq businesses based on the perspective of maqashid sharia. This study uses Partial Least Square analysis techniques. The sample used in this study were 75 small-scale traders (Mustahiq) assisted by LAZNAS Al-Azhar and LAZNAS Dompet Dhuafa in the Bogor Regency and Depok, West Java. The results show that funding and training provided by LAZNAS Al-Azhar and LAZNAS Dompet Dhuafa and knowledge possessed by Mustahiq significantly influence the success of mustahiq businesses.